2016
DOI: 10.18632/oncotarget.6841
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical regulation of the genome: global changes in nucleosome organization potentiate genome response

Abstract: Nucleosome occupancy is critically important in regulating access to the eukaryotic genome. Few studies in human cells have measured genome-wide nucleosome distributions at high temporal resolution during a response to a common stimulus. We measured nucleosome distributions at high temporal resolution following Kaposi's-sarcoma-associated herpesvirus (KSHV) reactivation using our newly developed mTSS-seq technology, which maps nucleosome distribution at the transcription start sites (TSS) of all human genes. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Assuming that adjacent nucleosomes (on the intergenic side of the RSS) are separated by distances similar to those detected for phased nucleosomes at transcription start sites (36,37), enough room is left for the 39 bp of the RSS (where the RSS is placed at coordinates 0 to +38) to be located off the histone core shoulder. Thus, in pro-B cells, the RSS would be either loosely associated with the nucleosome or in the linker region adjacent to the nucleosome, an ideal location that would allow access to the RAG recombinase (20,23).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Assuming that adjacent nucleosomes (on the intergenic side of the RSS) are separated by distances similar to those detected for phased nucleosomes at transcription start sites (36,37), enough room is left for the 39 bp of the RSS (where the RSS is placed at coordinates 0 to +38) to be located off the histone core shoulder. Thus, in pro-B cells, the RSS would be either loosely associated with the nucleosome or in the linker region adjacent to the nucleosome, an ideal location that would allow access to the RAG recombinase (20,23).…”
Section: Resultsmentioning
confidence: 93%
“…Variability in MNase profiles between experiments carried out under different conditions can hinder a direct comparison of absolute levels of nucleosome occupancy between cell types (35). However, the patterns across a locus can be readily compared between cell types, and a comparison of nucleosome occupancy across a locus within an individual cell type can be made (36)(37)(38)(39). Thus, our study focused on a comparison of relative values of nucleosome occupancy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we combined MNase-seq with in-solution targeted enrichment of 2 kb surrounding TSSs of 21,857 human genes (Druliner et al, 2016; Sexton et al, 2016), as curated by NCBI RefSeq (Pruitt et al, 2009). We termed this approach Transcription Start Site MNase-seq (mTSS-seq).…”
Section: Methodsmentioning
confidence: 99%
“…Micrococcal nuclease (MNase) was first used to isolate nucleosomal DNA from the chicken beta-globin gene (Sun et al, 1986). It remains the predominant method for generation of nucleosome occupancy maps in eukaryotic genomes, and previous studies have mapped changes in chromatin structure during differentiation, environmental stimulus or stress, and disease states (Shivaswamy et al, 2008; Teif et al, 2012; Druliner et al, 2013; Sexton et al, 2014, Sexton et al, 2016). Additionally, it has been recently shown that nucleosomes exhibit differential sensitivity to MNase.…”
Section: Introductionmentioning
confidence: 99%